Optimizing Contraceptive Counselling for Women with Migraine in a Primary Care Unit: A Quality Improvement Project - Vasconcelos, Rita; Sousa, Joana; Ribeiro, Joana; Pereira, Pedro; Alvarenga, Bárbara; Gomes, Mário; Sá, Maria (Gazeta Médica, 2025)
INTRODUCTION: Contraceptive counselling plays a crucial role in Family Planning within Primary Healthcare. While combined hormonal contraceptives (CHC) are widely used, it is essential to consider alternatives for women diagnosed with migraine. The primary objective of this project is to ensure the appropriate prescription of contraceptives for women diagnosed with migraine within a Portuguese family health unit. METHODS: We conducted a retrospective study for continuous quality improvement, including women diagnosed with migraine, regardless of aura presence, using CHC, or with outdated records (?3 years), irrespective of the contraceptive method in use. A multidisciplinary clinical session was held to discuss the issue and propose corrective strategies. Individual appointments were scheduled with the family physician for eligible women. A comparative analysis was subsequently carried out. A proportion of women correctly medicated with progestin contraception or non-hormonal methods ?70% and ?95% were considered "desirable" and "excellent," respectively. A value <70% was defined as "insufficient." RESULTS: Fifty-four eligible patients were identified, and after discussing risks and benefits, 83.3% (n=45) opted to change their contraceptive method. The majority chose progestin contraception (50.0%; n=27), 11.1% preferred barrier methods (n=6), 5.6% opted for intrauterine devices (n=3), and 16.6% chose no contraceptive method (n=9). A desired percentage of correctly medicated patients (83.3%) was achieved. CONCLUSION: This project underscores the importance of appropriate contraceptive counselling for women with migraine, demonstrating that motivated professionals can significantly enhance the quality of care provided in such contexts.